Gdynia Skwer Kościuszki/ fot. J. Uklejewski. - Uklejewski, Janusz (1925-2011) (Wyd. RUCH, 1960)
Przedstawia widok na Skwer Kościuszki i Molo Południowe ujęcie z ul. Świętojańskiej w kierunku morza, ok. 1965 r.